2015
DOI: 10.1617/s11527-015-0747-7
|View full text |Cite
|
Sign up to set email alerts
|

Chloride transport and the resulting corrosion of steel bars in alkali activated slag concretes

Abstract: As the relative performance of alkali activated slag (AAS) concretes in comparison to portland cement (PC) counterparts for chloride transport and resulting corrosion of steel bars is not clear, an investigation was carried out and the results are reported in this paper. The effect of alkali concentration and modulus of sodium silicate solution used in AAS was studied. Chloride transport and corrosion properties were assessed with the help of electrical resistivity, non-steady state chloride diffusivity, onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(100 citation statements)
references
References 27 publications
(47 reference statements)
11
82
1
Order By: Relevance
“…The specimens were totally immersed in the alkaline medium, and no oxygen entered into the specimen, and this led to strongly reducing conditions where sulfide was the dominant redox-active species. Moreover, any available oxygen can be consumed locally by the sulfide species becoming oxidized, either in part or in full (Holloway and Sykes, 2005;Ma et al, 2016). In those aqueous systems, where aqueous sulfide is in excess over Fe 3+ , iron is partially reduced and the Fe 2+ generated can react with S 2− to precipitate as FeS (Wan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The specimens were totally immersed in the alkaline medium, and no oxygen entered into the specimen, and this led to strongly reducing conditions where sulfide was the dominant redox-active species. Moreover, any available oxygen can be consumed locally by the sulfide species becoming oxidized, either in part or in full (Holloway and Sykes, 2005;Ma et al, 2016). In those aqueous systems, where aqueous sulfide is in excess over Fe 3+ , iron is partially reduced and the Fe 2+ generated can react with S 2− to precipitate as FeS (Wan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…However, fewer studies have been published regarding the actual corrosion process of steel embedded in alkali activated slag mortars in the presence of chloride (Holloway and Sykes, 2005;Torres Gomez et al, 2010;Park et al, 2015;Ma et al, 2016). AAS mortars activated with Ca(OH) 2 presented a higher corrosion resistance than AAS mortars activated with KOH and NaOH activators, which was attributed to the formation of Ca(OCl) 2 to remove free chloride from the pore solution, and thus to mitigate the corrosion risk (Park et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, elemental sulfur could play a role in inhibiting pitting corrosion only if sufficient oxygen is available at the SCI. Higher corrosion rates [48], higher i corr and lower R p values [42,49] have been reported for steel-reinforced AAS exposed to chloride solutions in comparison to those observed in PC. However, visual examination of the steel rebars in each of these studies found that the extent of corrosion for steel embedded in AAS was much lower than those in PC, for instance, no evidence of corrosion was observed by Criado et al [42], Fig.5, which contrasts strongly with the electrochemical observations.…”
Section: Binders With a Reducing Internal Environmentmentioning
confidence: 99%
“…The drop in the redox potential is a result of the release of reductants from the slag during its reaction (whether induced by alkali activation or in PC blends), and the inability of the cathode to generate a current that overcomes the HSoxidation peak. Ma et al [31] reported that the corrosion rate generally decreased with an increase in the concentration of sulfide due to the generation of a strongly reducing environment.…”
Section: Evolution Of Corrosion Potentialmentioning
confidence: 99%